Mendongkrak Volume Penjualan Produk UMKM Melalui Akun Organisasi E-Commerce - Fauziyah, Fauziyah; Rijalus Sholihin, Muhammad (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2019)
Indonesia is a big country, based on the Population Census data released by the Central Statistics Agency (BPS), the number of inhabitants in 2018 is not less than 260 million. This figure will continue to grow each year, projected in 2035 the number reached more than 300 million inhabitants. The existence and role of MSMEs (Micro, Small and Medium Enterprises) in supporting national economic activity, especially in addressing the problems of poverty, unemployment, inequality between sectors, is very important and strategic. Therefore, a strengthening of the economy of small and medium priority towards the creation of a solid economic fundamentals. However, in realizing the great potential, SMEs still face many problems, both internally and externally. The purpose of this study was to determine the extent of product variety, posting and updating, as well as keywords affect the increase in sales volume either partially or simultaneously. The method used in this penelitiaan is quantitative descriptive. The results of this study indicate that the product variety, posting and updating, as well as keywords affect the increase in sales volume either partially or simultaneously.